Learning Style Preferences Among Degree Students in Academic English Course in UTHM - Mohd Junaid, Thuwaibah; Nur Afiqah Ismail, Nadia (International Journal of Engineering and Technology, 2018)
This study was conducted to identify the major learning style preference among UTHM degree students semester 2 2015/2016 in Academic English classroom as well as to identify the differences between the learning style preferences of male and female students. A total of 150students from eight different faculties comprised of 75 male and 75 female students were involved in this study. The Perceptual Learning Style Preferences Questionnaire (PLSPQ) which was developed by Reid (1987) has been used as the instrument of the study. The findings revealed that the major learning style preference of the students was Kinesthetic learning style. Moreover, the findings also revealed that there were no significance differences at Î± = 0.05 between the learning styles preference of male and female UTHM degree studentsâ€™ semester 2 2015/2016 in Academic English classroom.Â Â